PERANCANGAN STAND DRUM SET DENGAN KONSEP TEMA TULANG BELULANG MANUSIA - Fauzi, Muhammad; Pernanda, Fajar Megi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
This writing aims to create a product drum set design for band musicians, especially drummer, especially in metal bands, to support their performances on stage with the theme of human bones. The concept is based on the views of various genres of music in the world where the metal music genre is the most powerful in terms of concept, such as the identity of the elements of death, human skull, blood, demons, and so on that still nuanced horror in it. In addition, the element of postmodernism to the design is strongly reinforced in its application because almost all parts of the drum booth is changed in order to maximize the theme that is carried except in function. In addition the drum stand concept is described in the form of prototype size of approximately 60cm.